Nasal biomarker testing to rule out viral respiratory infection and triage samples: a test performance study - Amat, Julien A.R.; Dudgeon, Sarah N.; Cheemarla, Nagarjuna R.; Watkins, Timothy A.; Green, Alex B.; Young, H. Patrick; Peaper, David R.; Landry, Marie L.; Schulz, Wade L.; Foxman, Ellen F. (EBioMedicine, 2025)
The COVID-19 pandemic revealed an urgent need for practical screening tests to rule out respiratory virus infection, both for managing outbreaks and for routine screening in high-risk settings. PCR is the gold standard test for respiratory virus diagnosis but requires specialised equipment, uses different assays for each virus, and often excludes emerging viruses. The goal of this study was to evaluate a pan-viral host biomarker to rule out respiratory virus infection. We used CXCL10, a cytokine induced in the nasal mucosa in response to diverse respiratory viruses. We compared immunoassay for CXCL10 to respiratory virus PCR panel results in 1088 nasopharyngeal samples from adults and children with an overall viral prevalence of 32.6% by PCR. Using this data, we mathematically modelled the impact of CXCL10 biomarker testing on patient triage and resource savings at different viral prevalences. We also explored clinical features associated with false negatives using automated data extraction from electronic medical records. CXCL10 accurately predicted virus positivity (A.U.C. 0.87, 95% C.I. 0.85–0.90). Mathematical modelling predicted that CXCL10 screening would enable a significant reduction in PCR testing, especially when viral prevalence is low (e.g. 92% of samples testing negative when viral prevalence is 5%, NPV = 0.975). Outlier analysis identified specific chemotherapeutic drugs and low viral load as features associated with false negatives. These results demonstrate the utility of a nasopharyngeal biomarker to rule out respiratory infection, with potential applications in outbreak management and/or routine screening in high-risk settings. Yale-New Haven Hospital Innovation Fund and NIH.